PENGELOLAAN KANTIN BERBASIS BUDAYA HIDUP SEHAT MELALUI PEMANFAATAN VOUCHER FOOD SEBAGAI ALAT TRANSAKSI DI SEKOLAH DASAR - Ayu Putri Ivana; Tansa Giri Asmaniah; Faridatun Nashiroh; Fitri Puji Rahmawati; Anatri Desstya; Honest Umi Kultsum (Buletin Literasi Budaya Sekolah, 2021)
Healthy living culture is a concept of life by prioritizing various life activities based on a healthy lifestyle.  The purpose of this study was to determine canteen management based on a healthy living culture through the use of food vouchers as a transaction tool in elementary schools.  Food vouchers are a means of substituting money for students to buy food or drinks at the SD Muhammadiyah Simo Special Program canteen.  Thus, it is not possible for students to buy food outside the school environment. The data analysis technique of this research is carried out inductively which goes from fact to theory, with the intention of avoiding data manipulation. Then, to test the validity of the data, it was done using triangulation of data learning techniques. This research uses qualitative methods through interviews, documentation and observation.  The research found that there is a management of food vouchers in the canteen towards a culture of healthy living in an elementary school environment. Based on the results of interviews conducted at the SD Muhammadiyah Simo Special Program, the school implemented the use of food vouchers to minimize children buying food from outside of school.  That way, students' health will be more secure.  The parents also fully support the provision of food vouchers, they feel safer because the school canteen provides healthy food without harmful ingredients.